Peran Kemampuan Manajerial dalam Memfasilitasi Transformasi Digital: Mendorong Transformasi Model Bisnis dan Peningkatan Kinerja Perusahaan - Sahetapy, Willyan; Biay, Agustinus; Rusdi (Jurnal Manajemen Sistem Informasi (JMASIF), 2026)
Digital transformation plays a central role in reshaping business models and improving company performance in today’s technological era. This study aims to analyze how managerial capabilities support digital transformation, driving changes in business models and organizational performance. Managers with strong leadership skills and strategic decision-making abilities are crucial in helping companies adapt to technological changes. The findings show that entrepreneurial skills have a positive impact on digital business model transformation (DBMT) and company performance, while leadership skills do not directly influence performance. Furthermore, managerial social capital strengthens the relationship between entrepreneurial skills and DBMT. Managerial cognition also plays a role in decision-making related to digitalization, although its impact varies between junior and senior managers. Effective managerial capabilities in managing change and technology are key to ensuring that companies remain competitive and adaptable in an ever-evolving market.